Pd‐Catalyzed Atropselective C−H Olefination Promoted by a Transient Directing Group. Issue 4 (29th December 2021) - Kumar, Rohit; Chandra, Devesh; Sharma, Upendra
Abstract: A Pd(II)‐catalyzed atropselective olefination of biaryls with maleimides is reported using chiral transient directing group (CTDG) strategy L‐ tert ‐leucine is used as a chiral auxiliary to obtain atropselective biaryl aldehydes with enantiomeric excess ranging from 70 to 99%. The method is also applicable for other olefins such as acrylonitrile, phenyl vinyl sulfone, and N ‐ tert ‐butyl acrylamide, providing corresponding atropselective biaryl aldehydes with 97–99% ee . Non‐linear effect studies suggest that chiral auxiliary is responsible for the atropselectivity of products. Other studies suggested the critical role of reaction time on yield and s‐factor of desired products. Abstract :